Carbon nanotubes as nanovectors for intracellular delivery of laronidase in Mucopolysaccharidosis type I. Issue 2 (14th December 2017) - Da Ros, T.; Ostric, A.; Andreola, F.; Filocamo, M.; Pietrogrande, M.; Corsolini, F.; Stroppiano, M.; Bruni, S.; Serafino, A.; Fiorito, S.
Abstract : The first example of intracellular delivery of a therapeutic enzyme by means of CNTs, retaining its activity. Abstract : The immobilization of proteins on carbon nanotubes (CNTs) has been widely reported mainly for the preparation of sensors while the conjugation of enzymes for therapeutic purposes has scarcely been considered. Herein we report, to the best of our knowledge, the first example of intracellular delivery of a therapeutic enzyme by means of CNTs, retaining its activity. Mucopolysaccharidosis I is a rare genetic disease characterized by the deficiency or absence of the activity of the α-l -iduronidase (IDUA) enzyme. We evaluated the capacity of the recombinant form of the human IDUA enzyme, laronidase (Aldurazyme®), conjugated with CNTs to be internalized by fibroblasts from subjects affected with Mucopolysaccharidosis type I and the capacity of the enzyme to retain its activity after internalization. The enzyme was successfully delivered into the lysosomal space and the enzymatic activity of the conjugate was preserved after internalization up to 48 hours. This paves the way towards the use of such a kind of construct for therapeutic applications.